Effects of intrauterine and postnatal protein-calorie malnutrition on metabolic adaptations to exercise in young rats. - de-Mello, M. A. [UNESP] (My University, 1994)
The effect of intrauterine and postnatal protein-calorie malnutrition on the biochemical ability to perform exercise was investigated in young male rats. Malnourished rats were obtained by feeding dams a low-protein (6%) casein-based diet prepared in the laboratory during pregnancy and lactation. Control rats received an isocaloric diet containing 25% protein. The low-protein diet contained additional starch and glucose. At 45 days of age, malnourished rats showed lower body weight, serum protein, albumin and glucose levels, hematocrit values and heart glycogen content but higher circulating free fatty acids and gastrocnemius muscle glycogen than control rats. In response to exercise (50 min of swimming), control rats displayed lower heart, gastrocnemius and liver glycogen levels whereas malnourished rats showed low glycogen levels only in the gastrocnemius muscle. Both control and malnourished rats showed high serum glucose and free fatty acid levels after exercise. In conclusion, protein-calorie malnutrition improved muscle glycogen storage but this substrate was broken down to a greater extent in response to exercise. Malnourished rats were able to perform exercise maintaining high blood glucose levels, as observed in control rats, perhaps as a consequence of the elevated availability of circulating free fatty acids.